Efficient flexible phase change heat storage building membrane material and preparation method thereof

By adding self-assembly, thermal fillers and chopped fibers of polyvinyl alcohol and polyacrylic acid to the phase change heat storage building film materials, the problems of high rigidity and low thermal conductivity of existing phase change heat storage film materials are solved, and efficient, flexible and high thermal conductivity building film materials are achieved, which are suitable for thermal energy management of complex building structures.

CN119684806AInactive Publication Date: 2025-03-25JIANGSU KEDEBON BUILDING ENERGY-SAVING TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510011571.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-04
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing phase change heat storage film materials are highly rigid and cannot adapt to complex building structures. They have low thermal conductivity, which affects the efficiency of thermal energy management.

Method used

The efficient flexible phase change heat storage building film material obtained by placing the phase change components in two pieces of release film is used to roll the composition, including phase change materials, matrix materials, thermal fillers and chopped fibers. Through self-assembly of polyvinyl alcohol and polyacrylic acid, the introduction of thermal fillers and the mixing of chopped fibers, the flexibility, thermal conductivity and toughness of the material are improved.

Benefits of technology

It realizes the efficient flexibility and high thermal conductivity of phase-change heat storage building membrane materials, which is suitable for the installation and adjustment of complex building structures, while improving the efficiency of thermal energy management.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an efficient flexible phase-change heat storage building membrane material and a preparation method thereof.The phase-change heat storage building membrane material is obtained by placing a phase-change component in two release membranes to be rolled, and the phase-change component is prepared from, by weight, 60-85 parts of a phase-change material, 15-28 parts of a matrix material, 12-23 parts of heat conduction filler and 2-3 parts of chopped fibers; the matrix material comprises silicone rubber, ethylene propylene diene monomer, polyvinyl alcohol and polyacrylic acid, and the weight mixing ratio of the polyvinyl alcohol to the polyacrylic acid is 1: 1-2: 1. According to the invention, polyvinyl alcohol and polyacrylic acid with a proper proportion are added into the phase change component, polyvinyl alcohol and polyacrylic acid have self-assembly ability and can be self-assembled into a nano or micron structure in a solution, and polyvinyl alcohol and polyacrylic acid can form a net shape among molecules due to electrostatic force among the molecules, so that the phase change effect is improved; therefore, the heat storage phase change building membrane has high flexibility and reversibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of phase-change architectural membranes, and in particular to a high-efficiency flexible phase-change heat storage architectural membrane material and a preparation method thereof. Background Art

[0002] Phase change materials refer to materials that can change their state and provide latent heat without changing the temperature. Phase change thermal storage film materials are widely used in building energy conservation as a medium for efficient thermal energy storage and temperature control. The use of phase change thermal storage film materials in buildings can not only save energy, but also significantly improve the insulation effect, help to more effectively store and manage thermal energy, thereby improving the energy efficiency of buildings.

[0003] The phase change heat storage film materials used in buildings in the prior art are usually rigid for the sake of structural strength. However, the rigid phase change heat storage film materials cannot be flexibly applied to different building structures, which makes the installation and adjustment of the rigid phase change heat storage film materials for complex structure buildings very troublesome, thereby requiring a flexible phase change heat storage building membrane material.

[0004] The defects of existing rubber surface treatment are: 1. The phase change membrane materials used in buildings in the prior art are rigid but not flexible, and cannot adapt to various complex building designs and construction requirements; 2. Patent document CN112210096A discloses a method for continuously producing a high-performance phase-change heat storage film. The production method of the heat storage film in this patent document is simple, but the heat storage film in this patent document does not consider improving the tensile strength and toughness of the phase-change film; 3. The solid-liquid phase change membrane materials in the prior art have solid-liquid changes during the phase change process, which can lead to problems such as difficulty in installation and easy leakage; 4. Patent document CN114834115B proposes a phase-change energy storage flexible film material and a preparation method thereof. However, the phase-change energy storage flexible film in the patent document does not consider improving the thermal conductivity of the phase-change film so that it can conduct heat efficiently. Summary of the invention

[0005] The object of the present invention is to provide a highly efficient and flexible phase-change thermal storage architectural membrane material and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions: a highly efficient and flexible phase-change heat storage architectural membrane material, wherein the phase-change heat storage architectural membrane material is obtained by placing a phase-change component in two release films and rolling them, wherein the phase-change component comprises the following raw materials in parts by weight: 60 to 85 parts of phase-change material, 15 to 28 parts of matrix material, 12 to 23 parts of thermal conductive filler and 2 to 3 parts of short-cut fibers; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of polyvinyl alcohol to polyacrylic acid is 1:1 to 2:1.

[0007] Preferably, the thermally conductive filler comprises carbon nanotubes and expanded graphite.

[0008] Preferably, the phase change material includes paraffin and stearic acid, and the phase change material also includes one or more of microcapsules, polyethylene glycol, and phase change polyols, and the phase change material is in granular form.

[0009] Preferably, the constituent fibers of the chopped fibers are mixed chopped fibers of carbon fibers or aramid fibers.

[0010] Preferably, the weight mixing ratio of carbon fiber and aramid fiber in the mixed chopped fibers is 5:3 to 5:2.

[0011] Preferably, the phase change component further includes a plasticizer, the mass fraction of the plasticizer in the phase change component is 1% to 2%, and the plasticizer is diisononyl phthalate.

[0012] Preferably, the phase change component density of the phase change heat storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change heat storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change heat storage architectural membrane material is 90J / g~220J / g.

[0013] Preferably, a method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material specifically comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0014] Preferably, the stirring speed in step S1 is 650 rpm to 900 rpm, and the stirring and mixing time is 15 min to 30 min; and the preheating target temperature in step S3 is 120° C. to 140° C.

[0015] Preferably, in step S4, the rolling speed is 1 mm / s to 5 mm / s, and the rolling time is 3 min to 8 min.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention adds polyvinyl alcohol and polyacrylic acid in appropriate proportions to the phase change components. Polyvinyl alcohol and polyacrylic acid have self-assembly capabilities and can self-assemble into nano or micro structures in a solution. Polyvinyl alcohol and polyacrylic acid can form a network between molecules due to the electrostatic force between molecules, thereby making the heat storage phase change architectural membrane have higher flexibility and reversibility.

[0017] 2. The present invention mixes a flexible matrix material and chopped fibers so that the phase change architectural membrane material has both sufficient tensile strength and certain flexibility. The chopped fibers can increase the thermal stability of the phase change material, making it less likely to deform or damage in a high temperature environment, thereby ensuring the effectiveness of the phase change process. At the same time, the chopped fibers can also increase the tensile strength and toughness of the heat storage phase change architectural membrane material. At the same time, the chopped fibers added in the present invention are carbon fibers and aramid fibers. The addition of carbon fibers can further improve the thermal conductivity of the phase change material, thereby achieving efficient heat storage.

[0018] 3. The chopped fibers in the present invention also include aramid fibers. The gel properties of aramid fibers can introduce thermal conductive fillers into the fiber web, allowing the phase change material to penetrate between the molecular webs formed by polyvinyl alcohol and polyacrylic acid. The unique packaging network of aramid fibers and thermal conductive fillers can hinder the leakage of the phase change material, thereby reducing the leakage rate of the phase change thermal storage architectural membrane material. At the same time, aramid fibers are soft in texture and strong in toughness, which can improve both the flexibility and toughness of the phase change thermal storage architectural membrane material.

[0019] 4. The EPDM rubber and silicone rubber in the present invention have a good effect on the encapsulation of organic phase change materials such as paraffin and stearic acid, and the thermally conductive fillers in the present invention are carbon nanotubes and expanded graphite. The addition of these thermally conductive fillers can significantly improve the thermal conductivity of the phase change thermal storage architectural membrane material and achieve efficient thermal conduction. The carbon nanotubes are nano-scale particles. The introduction of nano-scale particles can cause the phase change thermal storage architectural membrane material to produce a stress relaxation effect during the phase change process, thereby improving its flexibility. A plasticizer is also added in the present invention to further improve the toughness of the phase change thermal storage architectural membrane material. DETAILED DESCRIPTION

[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] If no specific experimental steps or conditions are specified in the examples, the operations or conditions of the conventional experimental steps described in the literature in the field shall be followed.

[0022] The present invention provides a high-efficiency flexible phase-change heat storage architectural membrane material, which is obtained by placing a phase-change component in two release films and rolling them, and the phase-change component includes the following raw materials in parts by weight: 60 to 85 parts of phase-change material, 15 to 28 parts of matrix material, 12 to 23 parts of thermal conductive filler and 2 to 3 parts of short-cut fibers; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of the polyvinyl alcohol and the polyacrylic acid is 1:1 to 2:1.

[0023] Thermally conductive fillers include carbon nanotubes and expanded graphite.

[0024] The phase change material includes paraffin and stearic acid, and the phase change material also includes one or more of microcapsules, polyethylene glycol, and phase change polyols. The phase change material is in granular form.

[0025] The constituent fibers of the chopped fibers are mixed chopped fibers of carbon fibers or aramid fibers.

[0026] The weight mixing ratio of the carbon fiber and the aramid fiber in the mixed chopped fibers is 5:3 to 5:2.

[0027] The phase change component also includes a plasticizer, and the mass fraction of the plasticizer in the phase change component is 1% to 2%, and the plasticizer is diisononyl phthalate.

[0028] The phase change component density of the phase change thermal storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change thermal storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change thermal storage architectural membrane material is 90J / g~220J / g.

[0029] A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0030] Among them, the stirring speed in step S1 is 650rpm~900rpm, and the stirring and mixing time is 15min~30min; the preheating target temperature in step S3 is 120℃~140℃; in step S4, the rolling speed is 1mm / s~5mm / s, and the rolling time is 3min~8min.

[0031] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0032] Embodiment 1: This embodiment provides a high-efficiency flexible phase-change heat storage architectural membrane material, which is obtained by placing a phase-change component in two release films and rolling them. The phase-change component includes the following raw materials in parts by weight: 75 parts of phase-change material, 20 parts of matrix material, 18 parts of thermal conductive filler and 2 parts of short-cut fibers; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of the polyvinyl alcohol and the polyacrylic acid is 1:1.

[0033] Thermally conductive fillers include carbon nanotubes and expanded graphite.

[0034] The phase change material comprises paraffin and stearic acid, the phase change material further comprises microcapsules and polyethylene glycol, and the phase change material is in particle form.

[0035] The constituent fibers of the chopped fibers are mixed chopped fibers of carbon fibers or aramid fibers.

[0036] The weight mixing ratio of carbon fiber and aramid fiber in the mixed chopped fibers is 5:3.

[0037] The phase change component also includes a plasticizer, and the mass fraction of the plasticizer in the phase change component is 1.5%, and the plasticizer is diisononyl phthalate.

[0038] The phase change component density of the phase change thermal storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change thermal storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change thermal storage architectural membrane material is 90J / g~220J / g.

[0039] A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0040] Among them, the stirring speed in step S1 is 650rpm~900rpm, and the stirring and mixing time is 15min~30min; the preheating target temperature in step S3 is 120℃~140℃; in step S4, the rolling speed is 1mm / s~5mm / s, and the rolling time is 3min~8min.

[0041] Embodiment 2: This embodiment provides a high-efficiency flexible phase-change heat storage architectural membrane material, which is obtained by placing a phase-change component in two release films and rolling them. The phase-change component includes the following raw materials in parts by weight: 75 parts of phase-change material, 20 parts of matrix material, 18 parts of thermal conductive filler and 2 parts of short-cut fibers; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of polyvinyl alcohol to polyacrylic acid is 2:1.

[0042] Thermally conductive fillers include carbon nanotubes and expanded graphite.

[0043] The phase change material comprises paraffin and stearic acid, the phase change material further comprises microcapsules and polyethylene glycol, and the phase change material is in particle form.

[0044] The constituent fibers of the chopped fibers are mixed chopped fibers of carbon fibers or aramid fibers.

[0045] The weight mixing ratio of carbon fiber and aramid fiber in the mixed chopped fibers is 5:3.

[0046] The phase change component also includes a plasticizer, and the mass fraction of the plasticizer in the phase change component is 1.5%, and the plasticizer is diisononyl phthalate.

[0047] The phase change component density of the phase change thermal storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change thermal storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change thermal storage architectural membrane material is 90J / g~220J / g.

[0048] A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0049] Among them, the stirring speed in step S1 is 650rpm~900rpm, and the stirring and mixing time is 15min~30min; the preheating target temperature in step S3 is 120℃~140℃; in step S4, the rolling speed is 1mm / s~5mm / s, and the rolling time is 3min~8min.

[0050] Embodiment three: This embodiment provides a high-efficiency flexible phase-change heat storage architectural membrane material, which is obtained by placing a phase-change component in two release films and rolling them. The phase-change component includes the following raw materials in parts by weight: 75 parts of phase-change material, 20 parts of matrix material, 18 parts of thermal conductive filler and 2 parts of short-cut fibers; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of the polyvinyl alcohol and the polyacrylic acid is 1:1.

[0051] Thermally conductive fillers include carbon nanotubes and expanded graphite.

[0052] The phase change material comprises paraffin and stearic acid, the phase change material further comprises microcapsules and polyethylene glycol, and the phase change material is in particle form.

[0053] The constituent fibers of the chopped fibers are mixed chopped fibers of carbon fibers or aramid fibers.

[0054] The weight ratio of carbon fiber to aramid fiber in the mixed chopped fibers is 5:2.

[0055] The phase change component also includes a plasticizer, and the mass fraction of the plasticizer in the phase change component is 1.5%, and the plasticizer is diisononyl phthalate.

[0056] The phase change component density of the phase change thermal storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change thermal storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change thermal storage architectural membrane material is 90J / g~220J / g.

[0057] A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material specifically comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0058] Among them, the stirring speed in step S1 is 650rpm~900rpm, and the stirring and mixing time is 15min~30min; the preheating target temperature in step S3 is 120℃~140℃; in step S4, the rolling speed is 1mm / s~5mm / s, and the rolling time is 3min~8min.

[0059] Embodiment 4: This embodiment provides a high-efficiency flexible phase-change heat storage architectural membrane material, which is obtained by placing a phase-change component in two release films and rolling them. The phase-change component includes the following raw materials in parts by weight: 75 parts of phase-change material, 20 parts of matrix material, 18 parts of thermal conductive filler and 2 parts of short-cut fibers; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of the polyvinyl alcohol and the polyacrylic acid is 1:1.

[0060] Thermally conductive fillers include carbon nanotubes and expanded graphite.

[0061] The phase change material comprises paraffin and stearic acid, the phase change material further comprises microcapsules and polyethylene glycol, and the phase change material is in particle form.

[0062] The constituent fibers of the chopped fibers are mixed chopped fibers of carbon fibers or aramid fibers.

[0063] The weight mixing ratio of carbon fiber and aramid fiber in the mixed chopped fibers is 5:3.

[0064] The phase change component also includes a plasticizer, the mass fraction of the plasticizer in the phase change component is 2%, and the plasticizer is diisononyl phthalate.

[0065] The phase change component density of the phase change thermal storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change thermal storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change thermal storage architectural membrane material is 90J / g~220J / g.

[0066] A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0067] Wherein, the stirring speed in step S1 is 650 rpm to 900 rpm, and the stirring and mixing time is 15 min to 30 min; and the preheating target temperature in step S3 is 120° C. to 140° C.

[0068] In step S4, the rolling speed is 1 mm / s to 5 mm / s, and the rolling time is 3 min to 8 min.

[0069] Comparative Example 1: This comparative example provides a high-efficiency flexible phase-change heat storage architectural membrane material, which is obtained by placing a phase-change component in two release films and rolling them, and the phase-change component includes the following raw materials in parts by weight: 75 parts of phase-change material, 20 parts of matrix material, 18 parts of thermal conductive filler and 2 parts of short-cut fibers; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of the polyvinyl alcohol and the polyacrylic acid is 1:1.

[0070] Thermally conductive fillers include carbon nanotubes and expanded graphite.

[0071] The phase change material comprises paraffin and stearic acid, the phase change material further comprises microcapsules and polyethylene glycol, and the phase change material is in particle form.

[0072] The constituent fibers of the chopped fibers are carbon fibers.

[0073] The phase change component also includes a plasticizer, and the mass fraction of the plasticizer in the phase change component is 1.5%, and the plasticizer is diisononyl phthalate.

[0074] The phase change component density of the phase change thermal storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change thermal storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change thermal storage architectural membrane material is 90J / g~220J / g.

[0075] A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material specifically comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0076] Among them, the stirring speed in step S1 is 650rpm~900rpm, and the stirring and mixing time is 15min~30min; the preheating target temperature in step S3 is 120℃~140℃; in step S4, the rolling speed is 1mm / s~5mm / s, and the rolling time is 3min~8min.

[0077] The difference between this comparative example and Example 1 is that the chopped fibers in this comparative example only contain carbon fibers, not mixed chopped fibers, and the rest are the same as Example 1.

[0078] Comparative Example 2: This comparative example provides a high-efficiency flexible phase-change heat storage architectural membrane material, which is obtained by placing a phase-change component in two release films and rolling them, and the phase-change component includes the following raw materials in parts by weight: 75 parts of phase-change material, 20 parts of matrix material, 18 parts of thermal conductive filler and 2 parts of short-cut fibers; Matrix materials include silicone rubber and EPDM rubber.

[0079] Thermally conductive fillers include carbon nanotubes and expanded graphite.

[0080] The phase change material comprises paraffin and stearic acid, the phase change material further comprises microcapsules and polyethylene glycol, and the phase change material is in particle form.

[0081] The constituent fibers of the chopped fibers are mixed chopped fibers of carbon fibers or aramid fibers.

[0082] The weight mixing ratio of carbon fiber and aramid fiber in the mixed chopped fibers is 5:3.

[0083] The phase change component also includes a plasticizer, and the mass fraction of the plasticizer in the phase change component is 1.5%, and the plasticizer is diisononyl phthalate.

[0084] The phase change component density of the phase change thermal storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change thermal storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change thermal storage architectural membrane material is 90J / g~220J / g.

[0085] A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0086] Among them, the stirring speed in step S1 is 650rpm~900rpm, and the stirring and mixing time is 15min~30min; the preheating target temperature in step S3 is 120℃~140℃; in step S4, the rolling speed is 1mm / s~5mm / s, and the rolling time is 3min~8min.

[0087] The difference between this comparative example and Example 1 is that the matrix material in this comparative example only includes silicone rubber and EPDM rubber, and does not include polyvinyl alcohol and polyacrylic acid. The rest is the same as Example 1.

[0088] Comparative Example 3: This comparative example provides a high-efficiency flexible phase-change heat storage architectural membrane material, which is obtained by placing a phase-change component in two release films and rolling them. The phase-change component includes the following raw materials in parts by weight: 75 parts of phase-change material, 20 parts of matrix material and 18 parts of thermal conductive filler; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of the polyvinyl alcohol and the polyacrylic acid is 1:1.

[0089] Thermally conductive fillers include carbon nanotubes and expanded graphite.

[0090] The phase change material comprises paraffin and stearic acid, the phase change material further comprises microcapsules and polyethylene glycol, and the phase change material is in particle form.

[0091] The weight mixing ratio of carbon fiber and aramid fiber in the mixed chopped fibers is 5:3.

[0092] The phase change component also includes a plasticizer, and the mass fraction of the plasticizer in the phase change component is 1.5%, and the plasticizer is diisononyl phthalate.

[0093] The phase change component density of the phase change thermal storage architectural membrane material is 0.8g / cm3~0.9g / cm3, the phase change temperature of the phase change thermal storage architectural membrane material is 28℃~46℃, and the enthalpy value of the phase change thermal storage architectural membrane material is 90J / g~220J / g.

[0094] A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material comprises the following steps: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

[0095] Among them, the stirring speed in step S1 is 650rpm~900rpm, and the stirring and mixing time is 15min~30min; the preheating target temperature in step S3 is 120℃~140℃; in step S4, the rolling speed is 1mm / s~5mm / s, and the rolling time is 3min~8min.

[0096] The difference between this comparative example and Example 1 is that short-cut fibers are not added in this comparative example, and the rest is the same as Example 1.

[0097] The compositions of the phase change components in Examples 1-4 and Comparative Examples 1-3 are as follows:

[0098] Performance test experiment: The phase change architectural membrane materials described in Examples 1-4 and Comparative Examples 1-2 were subjected to relevant performance tests according to conventional testing methods in the art, and the test results are as follows:

[0099] Combined with the above examples and comparative examples, and combined with the test results, analysis is performed: By comparing Examples 1-4 with Comparative Examples 1-3, the phase-change thermal storage architectural membrane material of the present invention has a higher thermal conductivity and can achieve efficient thermal management, and the phase-change thermal storage architectural membrane material of the present invention has a higher phase change enthalpy value, so that the architectural membrane material has good thermal management performance.

[0100] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A high-efficiency flexible phase-change thermal storage architectural membrane material, characterized in that: The phase-change heat storage architectural membrane material is obtained by placing a phase-change component in two release films and rolling them. The phase-change component includes the following raw materials in parts by weight: 60 to 85 parts of phase-change material, 15 to 28 parts of matrix material, 12 to 23 parts of thermal conductive filler and 2 to 3 parts of short-cut fibers; The matrix material comprises silicone rubber, ethylene propylene diene monomer rubber, polyvinyl alcohol and polyacrylic acid, wherein the weight mixing ratio of polyvinyl alcohol to polyacrylic acid is 1:1 to 2:

1.

2. The high-efficiency flexible phase-change thermal storage architectural membrane material according to claim 1, characterized in that: The thermal conductive filler includes carbon nanotubes and expanded graphite.

3. The high-efficiency flexible phase-change thermal storage architectural membrane material according to claim 1, characterized in that: The phase change material includes paraffin and stearic acid, and the phase change material also includes one or more of microcapsules, polyethylene glycol, and phase change polyols. The phase change material is in granular form.

4. The high-efficiency flexible phase-change thermal storage architectural membrane material according to claim 1, characterized in that: The constituent fibers of the chopped fibers are mixed chopped fibers of carbon fibers or aramid fibers.

5. The high-efficiency flexible phase-change thermal storage architectural membrane material according to claim 4, characterized in that: The weight mixing ratio of the carbon fiber and the aramid fiber in the mixed chopped fibers is 5:3 to 5:

2.

6. The high-efficiency flexible phase-change thermal storage architectural membrane material according to claim 1, characterized in that: The phase change component also includes a plasticizer, the mass fraction of the plasticizer in the phase change component is 1% to 2%, and the plasticizer is diisononyl phthalate.

7. The high-efficiency flexible phase-change thermal storage architectural membrane material according to claim 1, characterized in that: The phase change component density of the phase change heat storage architectural membrane material is 0.8g / cm3-0.9g / cm3, the phase change temperature of the phase change heat storage architectural membrane material is 28°C-46°C, and the enthalpy value of the phase change heat storage architectural membrane material is 90J / g-220J / g.

8. A method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material, according to any one of claims 1 to 6, characterized in that: The specific steps include: Step S1: pouring the phase change material, the matrix material, the thermal conductive filler and the chopped fibers into a mixer and stirring and mixing them at a high speed, and adding a plasticizer during the stirring and mixing process, and obtaining a basic mixture after high mixing; Step S2: pouring the basic mixture into a vacuum kneader preheated to 165° C., evacuating to 0.005 MPa to 0.008 MPa, heating to a temperature of 120° C. to 160° C., and stirring at the temperature for 50 min to 60 min to uniformly mix the various components, thereby obtaining a phase change composite material premix; Step S3: Laying two layers of release film on the roller of the calender in advance, and preheating the roller of the calender to the target temperature; Step S4: conveying the phase change composite material premix to a preheated roller for rolling, and sandwiching the phase change composite material film formed by calendering between two layers of release films to obtain a high-efficiency flexible phase change heat storage architectural membrane material.

9. The method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material according to claim 8, characterized in that: The stirring speed in step S1 is 650 rpm to 900 rpm, and the stirring and mixing time is 15 min to 30 min; the preheating target temperature in step S3 is 120° C. to 140° C.

10. The method for preparing a high-efficiency flexible phase-change thermal storage architectural membrane material according to claim 8, characterized in that: In step S4, the rolling speed is 1 mm / s to 5 mm / s, and the rolling time is 3 min to 8 min.

Citation Information

Patent Citations

  • Method for continuously producing high-performance phase change heat storage film

    CN112210096A

  • A flexible phase change energy storage membrane material and its preparation method

    CN114834115B